창의적 교실 분위기 평가 척도 개발 - 민지연(Ji Yeon Min); 최인수(In Soo Choi) (Korean Journal of child studies, 2008)
This study developed the Creative Classroom Climate Scale(CCCS) for Elementary Students, verified its validity and reliability, and examined relationships among creative thinking, personality and motivation. Three professionals examined the content validity of the CCCS after the items were developed by the researcher. The CCCS and the Creativity Inventory for Young Students(CIS; Choe & Lee, 2004) were administered to 266 6th grade students. Results showed that the CCCS was valid and reliable including the sub-factors of Support, Trust, Tension, Playfulness, Conflict, Challenge and Communication. The sub-factors correlated significantly with total scores. CIS scores varied by the creative climate of the classrooms on the CCCS; creative motivation was especially influenced by classroom climate.